Treatment withdrawal in relapsing−remitting multiple sclerosis: a retrospective cohort study. (26th July 2015) - Lus, G.; Signoriello, E.; Maniscalco, G. T.; Bonavita, S.; Signoriello, S.; Gallo, C.
Abstract : Background: To investigate the effect of drug withdrawal on the course of relapsing−remitting multiple sclerosis (RR‐MS). Methods: An observational cohort retrospective study was performed to compare the time to relapse of patients who discontinued disease‐modifying therapy (1a or 1b beta‐interferons or glatiramer acetate) with the patients who did not. One hundred and twenty‐eight RR‐MS patients were investigated using a time‐dependent approach. Results: Over a median follow‐up of 108 months, 60 patients discontinued treatment and 89 relapses were observed. The time to relapse was shorter in patients who discontinued treatment compared with those who did not ( P  < 0.001), median times being 31.1 months (95% confidence interval 10.4–50.8) and 85.8 months (95% confidence interval 58.6–106.3), respectively, whilst the baseline covariates (gender, Expanded Disability Status Scale at diagnosis) did not significantly affect the prognosis. Conclusions: It was found that stopping treatment strongly reduces the time to relapse and this information may be useful in patient management.